Pengaruh Kunjungan Wisatawan Mancanegara, Wisatawan Domestik, Jumlah Hotel dan Akomodasi Lainnya Terhadap Pendapatan Asli Daerah (PAD) di Kabupaten Badung Tahun 2001-2012 - Amerta, I Gusti Ngurah Oka; Budhiasa, I Gede Sudjana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 3, No. 2, Februari 2014 (pp. 48 - 76), 2014)
Regional income is a regional financial resources from the relevant local area. This study aims to determine the influence the number of foreign tourist visiting, the number of domestic tourist visiting, hotels to the number of hotels and other accomodation in Badung, and determine the effect number of foreign tourist visiting, domestic tourist visiting, number of hotels and other accomodation to regional income in Badung years 2001-2012.  Sampling in this study using Bootstrapping and than processed using computer programs Eviews and Lisrel 8.80 with path analysis technique. The analysis showed that the number of foreign tourist visiting effect is positive and significant, the number of domestic tourist visiting effect is negative and not significant to the number  hotel and others accomodation. The number of foreign tourist visiting effect is positive and significant, the number of domestic tourist visiting effect is negative and significant, the number of hotel and others accomodation effect is negative and not significant to regional income in Badung years 2001-2012. So the infrastructure that supports the development of tourism in Bali especially Badung should be increased.
Keywords: Tourism; hotel; foreign tourist; domestic tourist